Double Single-Crystal-to-Single-Crystal Transformation and Small-Molecule Activation in Rhodium NHC Complexes - Zenkina, Olena V.; Keske, Eric C.; Wang, Ruiyao; Crudden, Cathleen M. (Angewandte Chemie International Edition, 2011)
Three gases, one crystal: Rhodium NHC complexes undergo back‐to‐back single‐crystal‐to‐single‐crystal transformations by selective nonreversible ligand exchange reactions (see picture). Slow diffusion of O2 converts a dinitrogen complex into a dioxygen complex, and CO subsequently replaces O2.